Software Standards for the Multicore Era - Holt, J.; Agarwal, A.; Brehmer, S.; Domeika, M.; Griffin, P.; Schirrmeister, F. (IEEE MICRO, 2009)
Systems architects commonly use multiple cores to improve system performance. Unfortunately, multicore hardware is evolving faster than software technologies. New multicore software standards are necessary in light of the new challenges and capabilities that embedded multicore systems provide. The newly released multicore communications API standard targets small-footprint, highly efficient intercore and interchip communications.